Rat Hepatitis E Virus: Presence in Humans in South-Western France? - Parraud, Delphine; Lhomme, Sébastien; Péron, Jean Marie; Da Silva, Isabelle; Tavitian, Suzanne; Kamar, Nassim; Izopet, Jacques; Abravanel, Florence (Frontiers in Medicine, 2021)
Background: Hepatitis E Virus (HEV) is one of the most common causes of hepatitis worldwide, and South-Western France is a high HEV seroprevalence area. While most cases of HEV infection are associated with the species Orthohepevirus-A, several studies have reported a few cases of HEV infections due to Orthohepevirus-C (HEV-C) that usually infects rats. Most of these human cases have occurred in immunocompromised patients. We have screened for the presence of HEV-C in our region. Methods and Results: We tested 224 sera, mostly from immunocompromised patients, for HEV-C RNA using an in-house real time RT-PCR. Liver function tests gave elevated results in 63% of patients: mean ALT was 159 IU/L (normal < 40 IU/L). Anti-HEV IgG (49%) and anti-HEV IgM (9.4%) were frequently present but none of the samples tested positive for HEV-C RNA. Conclusion: HEV-C does not circulate in the human population of South-Western France, despite the high seroprevalence of anti-HEV IgG.